Mie Aceh : a Smes Halal Culinary Strategy in Jakarta - Marissa Grace Haque (Syntax Idea)
Mie Aceh is a halal SMEs business, which possible to continue to be sustainable, at any situation and condition, by incorporating all advancements in the digital realm into their operations, businesses can evolve and thrive. This research employs a mixed-method approach, featuring descriptive analysis, to identify the most efficient and effective strategy required. Utilizing a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) as the evaluation tool, with an "Internal-External" weighting step, coupled with a "Four-Step Strategy," the study aims to determine the appropriate business strategies for halal culinary SMEs, specifically "Mie Aceh “M." The objective is to assess the existing strengths of the SMEs, achieve sustainable business management goals, address identified weaknesses, capitalize on opportunities, and mitigate threats. It underscores the importance of digital marketing and product innovation to adapt to changing market dynamics. Furthermore, it suggests maintaining and expanding the "cost leadership strategy" previously implemented.